Filling material and preparation method and application thereof

By using rubber base material filling materials with porous structures, the problems of high weight and poor torque resistance of traditional cable filling materials are solved, and the effect of reducing cable weight and improving torque resistance is achieved.

CN118546468BActive Publication Date: 2025-02-14特变电工山东鲁能泰山电缆有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410629800.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2025-02-14
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

Traditional cable filling materials use high-temperature fiberglass ropes, which leads to high weight and poor torque resistance, which cannot meet the requirements of wind power cables.

Method used

A filler material with a porous structure is used, which consists of a rubber substrate and a crosslinking filler dispersed in the rubber substrate. By controlling the porosity and pore structure diameter, the mechanical properties of the material are improved.

Benefits of technology

It reduces the overall quality of the filling material, improves torsion resistance and fatigue resistance, reduces the impact of vibration on the wire core, and extends the service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118546468B_ABST
    Figure CN118546468B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of rubber technology, and provides a filling material and a preparation method and application thereof, wherein the filling material has a porous structure and includes a rubber substrate and a first filler dispersed in the rubber substrate, wherein the first filler is cross-linked with the rubber substrate. The present application uses a rubber material as a substrate, and disperses a filler that can be cross-linked with the rubber substrate to form a filling material with a porous structure, which can not only reduce the overall mass of the filling material, but also improve the torsion resistance and fatigue resistance of the filling material due to the presence of the pore structure during the torsion process, reduce the impact of vibration on the wire core, and increase the service life of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of rubber technology, and in particular to a filling material and a preparation method and application thereof. Background Art

[0002] The cable core is composed of multiple twisted cores. During the cabling process, the gaps between the cores are filled with filling materials to ensure the roundness of the cable and avoid twisting of the cores. In traditional technology, the filling material usually uses high-temperature resistant glass fiber rope, which is an inorganic material with high density, resulting in high cable weight. In addition, the high-temperature resistant glass fiber rope has poor torsion resistance and cannot meet the requirements of wind power cables. Therefore, how to provide a filling material with light weight and good torsion resistance has become a technical problem that urgently needs to be solved. Summary of the invention

[0003] Based on this, an embodiment of the present application provides a filling material that is light in weight and has good torsional resistance, and a preparation method and application thereof.

[0004] In a first aspect, the present application provides a filling material having a porous structure. The filling material comprises a rubber base material and a first filler dispersed in the rubber base material, wherein the first filler is cross-linked with the rubber base material.

[0005] In some embodiments, the porosity of the filling material is 10% to 50%.

[0006] In some embodiments, the average diameter of the holes in the filling material is 1 mm to 2 mm.

[0007] In some embodiments, the rubber substrate includes at least one of ethylene propylene rubber, natural rubber, styrene butadiene rubber, chlorinated polyethylene rubber, silicone rubber and ethylene-vinyl acetate copolymer.

[0008] In some embodiments, the mass ratio of the rubber substrate to the first filler is (0.45-1):1.

[0009] In some embodiments, the first filler includes filler particles and a modifier grafted onto the surface of the filler particles, and the modifier is cross-linked with the rubber substrate.

[0010] In some embodiments, the filler particles include at least one of white carbon, montmorillonite, illite, bentonite, kaolin, and china clay.

[0011] In some embodiments, the modifying agent includes at least one of epoxidized soybean oil, epoxidized linseed oil, and epoxidized rapeseed oil.

[0012] In some embodiments, the mass ratio of the modifier to the filler particles is 1:(3-6).

[0013] In some embodiments, the filling material further comprises a second filler dispersed in the rubber base material.

[0014] In some embodiments, the second filler includes at least one of calcium carbonate, carbon black, talc, and clay.

[0015] In some embodiments, the mass ratio of the first filler to the second filler is (0.5-1.8):1.

[0016] In a second aspect, the present application provides a method for preparing the filling material as described in the first aspect, the method for preparing the filling material comprising:

[0017] The rubber raw material, the first filler for absorbing the foaming agent and the auxiliary agent are mixed and kneaded to prepare the filling material.

[0018] In some embodiments, the blowing agent includes water.

[0019] In some embodiments, the mass content of the blowing agent in the first filler that absorbs the blowing agent is 10% to 15%.

[0020] In some embodiments, the raw materials for preparing the filling material further include a second filler. In terms of mass fraction, the raw materials for preparing the filling material include:

[0021] 20~30 parts of rubber raw materials;

[0022] 35 to 50 parts of the first filler for absorbing the foaming agent;

[0023] 15 to 60 parts of the second filler; and

[0024] 10~21 parts of additives.

[0025] In some embodiments, the auxiliary agent includes at least one of a vulcanizing agent, an antioxidant, an activator, a plasticizer, and a coupling agent.

[0026] In some embodiments, the auxiliary agent includes a vulcanizing agent, an antioxidant, an activator, a plasticizer and a coupling agent. In terms of weight percentage, the raw materials for preparing the filling material include:

[0027] 20~30 parts of rubber raw materials;

[0028] 35 to 50 parts of the first filler for absorbing the foaming agent;

[0029] 15 to 60 parts of the second filler;

[0030] 2~3 parts of vulcanizing agent;

[0031] 1~2 parts of antioxidant;

[0032] Activator 5~11 parts;

[0033] 1 to 3 parts of plasticizer; and,

[0034] 1~2 parts of coupling agent.

[0035] In a third aspect, the present application provides a use of the filling material as described in the first aspect in the preparation of power transmission products.

[0036] In a fourth aspect, the present application provides a cable, comprising the filling material as described in the first aspect.

[0037] Compared with the traditional technology, this application has at least the following beneficial effects:

[0038] The present application uses rubber material as a base material and disperses a filler that can cross-link with the rubber base material to form a filling material with a porous structure, which can not only reduce the overall mass of the filling material, but also reduce the influence of torsion compression on the mechanical properties of the material due to the presence of the pore structure during the torsion process, thereby improving the torsion resistance and fatigue resistance, reducing the influence of vibration on the wire core, and increasing the service life of the cable. In addition, the preparation material of the present application is made by foaming with an environmentally friendly modifier, and no toxic substances are generated during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of the structure of a cable provided in one embodiment of the present application.

[0040] Among them, 10-main line core; 11-main line conductor; 12-main line conductor shielding layer; 13-main line insulation layer; 14-main line insulation shielding layer; 20-ground wire core; 21-ground wire conductor; 22-ground wire conductor shielding layer; 30-filling material layer; 31-first filling structure; 32-second filling structure; 40-sheath layer. DETAILED DESCRIPTION

[0041] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0043] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0044] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0045] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0046] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0047] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the invention purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0048] In the traditional technology, fillers such as carbon black, graphite, kaolin and white carbon are directly filled between the wire cores of the cable, but the density of the inorganic filler is high, resulting in a large overall weight of the cable, which is inconvenient for cable installation and use. In addition, polymer materials can be blended with inorganic fillers such as carbon black, graphite, kaolin and white carbon as fillers, but the filler not only has the problem of poor dispersion effect of inorganic fillers, but also has poor torsion resistance and fatigue resistance. The present application has found that by modifying the filler and dispersing it into the rubber substrate, not only the dispersion effect is good but also the mechanical properties of the material can be improved. In addition, the porous structure formed can effectively reduce the weight of the material and has an energy absorption and shock absorption effect, effectively improving the service life of the cable.

[0049] In a first aspect, the present application provides a filling material having a porous structure. The filling material comprises a rubber base material and a first filler dispersed in the rubber base material, wherein the first filler is cross-linked with the rubber base material.

[0050] The present application uses a rubber material as a base material and disperses a filler that can cross-link with the rubber base material to form a filling material with a porous structure. This can not only reduce the overall mass of the filling material, but also improve the torsion resistance and anti-fatigue performance due to the presence of the pore structure during the torsion process, reduce the impact of vibration on the wire core, and increase the service life of the cable.

[0051] In some embodiments, the porosity of the filling material is 10% to 50%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.

[0052] In some embodiments, the average diameter of the pore structure in the filling material is 1 mm to 2 mm, for example, it can be 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm or 2.0 mm.

[0053] The present application controls the porosity and pore structure diameter of the filling material, thereby ensuring the mechanical strength of the filling material, and further ensuring the torsion resistance and fatigue resistance of the wind power cable during use.

[0054] In some embodiments, the rubber substrate includes at least one of ethylene propylene rubber, natural rubber, styrene butadiene rubber, chlorinated polyethylene rubber, silicone rubber and ethylene-vinyl acetate copolymer. Preferably, ethylene propylene rubber. Optionally, the ethylene propylene rubber includes at least one of ethylene propylene diene rubber and ethylene propylene diene rubber. The present application selects ethylene propylene rubber as the rubber substrate, which has the advantages of excellent electrical properties, good insulation properties and good processability.

[0055] In some embodiments, the mass ratio of the rubber substrate to the first filler is (0.45-1):1, for example, 0.45:1, 0.50:1, 0.55:1, 0.60:1, 0.65:1, 0.70:1, 0.75:1, 0.80:1, 0.85:1, 0.90:1, 0.95:1 or 1.00:1.

[0056] The present application selects a suitable mass ratio of the rubber base material to the first filler so that the filling material has good mechanical properties.

[0057] In some embodiments, the first filler includes filler particles and a modifier grafted onto the surface of the filler particles, and the modifier is cross-linked with the rubber substrate.

[0058] In some embodiments, the filler particles include at least one of white carbon black, montmorillonite, illite, bentonite, kaolin and clay, preferably white carbon black, which has a high surface hydroxyl content and is more compatible with the present formulation system.

[0059] In some embodiments, the modifier includes at least one of epoxidized soybean oil, epoxidized linseed oil and epoxidized rapeseed oil, preferably epoxidized soybean oil, which has low cost and good modification effect.

[0060] In some embodiments, the first filler is epoxy soybean oil-modified white carbon black. Optionally, the average particle size of the filler particles is 10 nm to 40 nm.

[0061] In this application, white carbon black modified with epoxidized soybean oil is used as the first filler. White carbon black is also known as amorphous hydrated nano-silica, and contains a large number of hydroxyl groups on the surface. Epoxidized soybean oil contains relatively active epoxy groups, which are easy to open the ring and react with the hydroxyl groups on the white carbon black, thereby grafting the epoxidized soybean oil on the surface of the white carbon black. Furthermore, epoxidized soybean oil can improve the dispersibility of white carbon black in EPDM rubber, and effectively improve the mechanical properties and low temperature resistance of the filling material.

[0062] In some embodiments, the mass ratio of the modifier to the filler particles is 1:(3-6), for example, 1:3.0, 1:3.3, 1:3.6, 1:3.9, 1:4.2, 1:4.5, 1:4.8, 1:5.1, 1:5.4, 1:5.7 or 1:6.0.

[0063] The present application appropriately selects the mass ratio of the modifier to the filler particles in the first filler, which not only makes the filler particles well dispersed during the preparation of the filling material, but also ensures that the surface functional groups of the first filler are tightly combined with the rubber matrix, thereby avoiding the occurrence of problems such as insufficient modification and precipitation of the modifier.

[0064] In some embodiments, the filling material further comprises a second filler dispersed in the rubber substrate. Optionally, the average particle size of the second filler is 1 μm to 20 μm, for example, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.

[0065] In some embodiments, the second filler includes at least one of calcium carbonate, carbon black, talc, and clay.

[0066] The present application further fills the rubber substrate with a second filler. The second filler has good compatibility and can be filled in the gaps between the rubber substrate, the first filler and other materials, which can not only improve the mechanical properties of the filling material but also effectively reduce the cost.

[0067] In some embodiments, the mass ratio of the first filler to the second filler is (0.5-1.8): 1, for example, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1.0: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, 1.6: 1, 1.7: 1 or 1.8: 1. The present application appropriately selects the mass ratio of the first filler to the second filler to effectively ensure the mechanical properties and porous structure of the filling material.

[0068] The second aspect of the present application provides a method for preparing the filling material as described in the first aspect, the method for preparing the filling material comprising:

[0069] The rubber raw material, the first filler for absorbing the foaming agent and the auxiliary agent are mixed and kneaded to prepare the filling material.

[0070] In the present application, the foaming agent is adsorbed on the first filler, and the foaming agent can be evenly mixed in the raw material as the first filler is dispersed, so that the formed porous structure is more uniform, and the foaming agent adsorbed in the first filler can be released in stages, so that the pore structure of the porous structure can be evenly dispersed and the pore structure size can be smaller, thereby avoiding the accumulation of the foaming agent leading to uneven dispersion of the pore structure or excessively large pore structure.

[0071] In some embodiments, the foaming agent includes water. The water used as the foaming agent is heated to form water vapor during the preparation of the filling material, thereby making the prepared filling material have a porous structure.

[0072] In some embodiments, the mass content of the foaming agent in the first filler for adsorbing the foaming agent is 10% to 15%, for example, it can be 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5% or 15.0%.

[0073] The present application controls the adsorption amount of the foaming agent in the first filler, thereby effectively ensuring the porosity and pore structure size of the formed filling material, so that the filling material has good torsion resistance and mechanical properties.

[0074] In some embodiments, the first filler for absorbing the foaming agent is epoxy soybean oil modified white carbon black that absorbs water. Among them, white carbon black contains a large number of hydroxyl groups, and the surface is very easy to absorb water. That is, water molecules can be adsorbed on the surface of white carbon black, and can also be combined with the surface hydroxyl groups of white carbon black to form hydrated silica molecules in the form of hydrogen bonds, so that during the mixing process, water molecules can be precipitated in stages to form a porous structure with small size and uniform dispersion. In addition, epoxy soybean oil modification can improve the dispersibility of white carbon black in the raw materials, and epoxy soybean oil can cross-link with rubber raw materials, thereby increasing the cross-linking density of rubber, increasing the molecular weight of rubber, and at the same time expanding the distance between rubber molecules to improve the formation of microporous structure, thereby effectively improving the mechanical properties and torsion resistance of the filling material.

[0075] In some embodiments, the method for preparing the water-absorbed epoxy soybean oil-modified white carbon black comprises:

[0076] The epoxy soybean oil and white carbon black are mixed and stirred at 100°C to 140°C for 5min to 15min, and the epoxy soybean oil is grafted on the surface of the white carbon black to obtain epoxy soybean oil-modified white carbon black;

[0077] The epoxy soybean oil-modified silica is placed in an environment with a humidity of 50% to 100% to adsorb water molecules to obtain the epoxy soybean oil-modified silica adsorbed with water; or, the epoxy soybean oil-modified silica is mixed and stirred with water to obtain the epoxy soybean oil-modified silica adsorbed with water.

[0078] In some embodiments, the epoxy soybean oil-modified white carbon black is dried before adsorbing water, and the temperature of the drying treatment is 100° C. to 120° C. The present application can remove excess water in the material without affecting the bound water by drying the epoxy soybean oil-modified white carbon black, thereby increasing the material adsorption amount during the water adsorption process; and the epoxy soybean oil-modified white carbon black can be optimized during the drying process, which can improve the filling effect and the cross-linking effect.

[0079] In some embodiments, the raw materials for preparing the filling material further include a second filler. In terms of mass fraction, the raw materials for preparing the filling material include:

[0080] 20~30 parts of rubber raw materials;

[0081] 35 to 50 parts of the first filler for absorbing the foaming agent;

[0082] 15 to 60 parts of the second filler; and

[0083] 10~21 parts of additives.

[0084] In some embodiments, the auxiliary agent includes at least one of a vulcanizing agent, an antioxidant, an activator, a plasticizer, and a coupling agent.

[0085] In some embodiments, the auxiliary agent includes a vulcanizing agent, an antioxidant, an activator, a plasticizer and a coupling agent. In terms of weight percentage, the raw materials for preparing the filling material include:

[0086] 20~30 parts of rubber raw materials;

[0087] 35 to 50 parts of the first filler for absorbing the foaming agent;

[0088] 15 to 60 parts of the second filler;

[0089] 2~3 parts of vulcanizing agent;

[0090] 1~2 parts of antioxidant;

[0091] Activator 5~11 parts;

[0092] 1 to 3 parts of plasticizer; and,

[0093] 1~2 parts of coupling agent.

[0094] For example, the mass fraction of the rubber raw material can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts. The mass fraction of the first filler that absorbs the foaming agent can be 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts. The mass fraction of the second filler can be 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts. The mass fraction of the vulcanizing agent can be 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3.0 parts. The mass fraction of antioxidant can be 1.0 part, 1.1 part, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts. The mass fraction of activator can be 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts, 10.0 parts, 10.5 parts or 11.0 parts. The mass fraction of plasticizer can be 1.0 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts or 3.0 parts. The mass fraction of the coupling agent can be 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts.

[0095] In some embodiments, the vulcanizing agent includes at least one of triallyl isocyanurate (TAIC) and dicumyl peroxide (DCP). Optionally, the vulcanizing agent includes triallyl isocyanurate (TAIC) and dicumyl peroxide (DCP). Further optionally, the mass ratio of triallyl isocyanurate (TAIC) to dicumyl peroxide (DCP) is (0.6-1.5):1.

[0096] In some embodiments, the antioxidant includes at least one of antioxidant RD, antioxidant 4010, and antioxidant MB.

[0097] In some embodiments, the activator comprises at least one of zinc oxide, stearic acid, magnesium oxide and zinc stearate. Optionally, the activator comprises zinc oxide and stearic acid. Further optionally, the mass ratio of zinc oxide to stearic acid is (1.3-8):1.

[0098] In some embodiments, the plasticizer includes at least one of paraffin, chlorinated paraffin, and environmentally friendly aromatic oil.

[0099] In some embodiments, the coupling agent includes at least one of silane coupling agents Si-69, Si-747 and A171, wherein the silane coupling agent Si-69 refers to bis-[γ-(triethoxysilyl)propyl] tetrasulfide.

[0100] In some embodiments, the raw materials for preparation include, by weight:

[0101] 20~30 parts of rubber raw materials;

[0102] 35 to 50 parts of the first filler for absorbing the foaming agent;

[0103] 10 to 40 parts of calcium carbonate;

[0104] Carbon black 5~20 parts;

[0105] Curing agent DCP 1~1.5 parts;

[0106] Co-vulcanizing agent TAIC 1 to 1.5 parts;

[0107] 1~2 parts of antioxidant;

[0108] 4 to 8 parts of zinc oxide;

[0109] 1 to 3 parts of stearic acid;

[0110] 1 to 3 parts of plasticizer; and,

[0111] 1~2 parts of coupling agent.

[0112] Exemplarily, a method for preparing the above-mentioned filling material is provided, comprising:

[0113] S1. Weigh the raw materials according to their mass fractions, and mix the rubber raw materials, antioxidant and activator for 1 min to 2 min;

[0114] S2, adding the first filler adsorbed with the foaming agent, the second filler and the coupling agent, and mixing for 3min~4min;

[0115] S3. When the mixing temperature reaches 90℃~110℃, discharge the internal mixer, pass the mixed rubber compound through the open mixer for 2~3 times, filter it with a filter, and calender it on a three-roll calender without cutting it into sheets. After the calendered rubber compound is stored at room temperature for 24 hours, put it into the internal mixer for mixing. When the mixing temperature is 90℃~110℃, add the vulcanizing agent, mix for another 0.5min~1min, and then discharge the material. After discharging, pass it through the open mixer for 1~2 times, and cut it into sheets on a three-roll calender. After cooling, roll it up and store it to obtain the filling material.

[0116] The third aspect of the present application provides a use of the filling material as described in the first aspect in the preparation of power transmission products.

[0117] A fourth aspect of the present application provides a cable, comprising the filling material as described in the first aspect.

[0118] In some embodiments, the cable includes a core, the filling material, and a sheath layer, wherein the sheath layer wraps a plurality of the cores, and the filling material is filled in the sheath layer.

[0119] In some embodiments, the wire cores are dispersedly arranged, and the filling material is also filled between the wire cores.

[0120] In some embodiments, Figure 1 As shown, the cable includes a core, a filling material layer 30 and a sheath layer 40, the core includes a main core 10 and a ground core 20, the main core 10 includes a main conductor 11 and a main conductor shielding layer 12, a main insulation layer 13 and a main insulation shielding layer 14 sequentially coated on the outside of the main conductor 11, and the ground core 20 includes a ground conductor 21 and a ground conductor shielding layer 22 coated on the outside of the ground conductor 21. The filling material layer 30 includes the filling material, the filling material layer includes a first filling structure 31 filled between the main core 10 and the ground core 20, the first filling structure 31 is saddle-shaped, and the filling material layer 30 also includes a second filling structure 32 filled between the sheath layer 40 and the main core 10 and the ground core 20.

[0121] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0122] In the following examples and comparative examples, the average particle size of the precipitated silica is 20 nm, the average particle size of the carbon black is 5 μm, and the average particle size of the calcium carbonate is 10 μm.

[0123] The EPDM rubber was purchased from Jilin Petrochemical with a brand number of 4045.

[0124] Example 1

[0125] Water-adsorbed Epoxidized Soybean Oil Modified Silica

[0126] Epoxidized soybean oil and white carbon black were mixed in a mass ratio of 1:5, and shear-stirred for 10 min at 120° C. to obtain epoxy soybean oil-modified white carbon black;

[0127] First, the epoxy soybean oil modified silica was dried at 100°C for 10 minutes, and then the epoxy soybean oil modified silica was placed in a constant temperature and humidity environment (temperature of 50°C, humidity of 80%) to naturally adsorb water molecules to obtain water-adsorbed epoxy soybean oil modified silica. The mass of the adsorbed water was 15% of the total mass of the water-adsorbed epoxy soybean oil modified silica. After preparation, it was stored in a sealed bag for later use.

[0128] Filling material

[0129] S1. Weigh the raw materials for preparation according to the mass fraction, including:

[0130] 25 parts of EPDM rubber;

[0131] 35 parts of water-absorbed epoxy soybean oil-modified white carbon black;

[0132] 15 parts of calcium carbonate;

[0133] 10 parts of carbon black;

[0134] 1.5 parts of vulcanizing agent DCP;

[0135] 1 part of co-vulcanizing agent TAIC;

[0136] Anti-aging agent RD 2 parts;

[0137] Zinc oxide 5 parts;

[0138] 2 parts of stearic acid;

[0139] 2 parts paraffin; and,

[0140] Coupling agent Si-69 1.5 parts.

[0141] Put EPDM rubber into internal mixer according to the formula ratio, then add antioxidant RD, zinc oxide and stearic acid, and mix for 1.5 minutes;

[0142] S2, adding water-absorbed epoxy soybean oil-modified white carbon black, calcium carbonate, carbon black and coupling agent Si-69, and mixing for 4 minutes;

[0143] S3. When the mixing temperature reaches 100°C, discharge the material from the internal mixer. Pass the mixed rubber material through the open mixer for three times, filter it with a filter, and calender it on a three-roll calender without slitting it into sheets. After slitting, store the rubber material at room temperature for 24 hours and then put it into the internal mixer for mixing. When the mixing temperature is 110°C, add the vulcanizing agent DCP and the co-vulcanizing agent TAIC, mix for 1 minute and discharge the material. After discharging, pass the material through the open mixer for two times, calender it on a three-roll calender to slid it into sheets. The output rubber sheet is cooled by a cooling roller, rolled up and stored to obtain a filling material with a porous structure.

[0144] Example 2

[0145] The filling material is prepared according to the method of Example 1, the only difference being that the raw materials for preparation include:

[0146] 20 parts of EPDM rubber;

[0147] 45 parts of water-absorbed epoxy soybean oil-modified white carbon black;

[0148] 15 parts of calcium carbonate;

[0149] 5 parts of carbon black;

[0150] 1.5 parts of vulcanizing agent DCP;

[0151] 1 part of co-vulcanizing agent TAIC;

[0152] Anti-aging agent RD 2 parts;

[0153] Zinc oxide 5 parts;

[0154] 2 parts of stearic acid;

[0155] 2 parts paraffin; and,

[0156] Coupling agent Si-69 1.5 parts.

[0157] Among them, the amount of water adsorbed in the epoxy soybean oil modified silica is 10%, and the mass ratio of epoxy soybean oil to silica is 1:3.

[0158] Example 3

[0159] The filling material is prepared according to the method of Example 1, the only difference being that the raw materials for preparation include:

[0160] 30 parts of EPDM rubber;

[0161] 50 parts of water-absorbed epoxy soybean oil-modified white carbon black;

[0162] 15 parts of calcium carbonate;

[0163] 5 parts of carbon black;

[0164] 1.5 parts of vulcanizing agent DCP;

[0165] 1 part of co-vulcanizing agent TAIC;

[0166] Anti-aging agent RD 2 parts;

[0167] Zinc oxide 5 parts;

[0168] 2 parts of stearic acid;

[0169] 2 parts paraffin; and,

[0170] Coupling agent Si-69 1.5 parts.

[0171] Among them, the amount of water adsorbed in the epoxy soybean oil modified silica is 13%, and the mass ratio of epoxy soybean oil to silica is 1:6.

[0172] Example 4

[0173] The filling material was prepared according to the method of Example 1, with the only difference being that the mass proportion of water in the epoxy soybean oil-modified silica that adsorbed water was 5%.

[0174] Example 5

[0175] The filling material was prepared according to the method of Example 1, except that the mass proportion of water in the epoxy soybean oil-modified silica that adsorbed water was 10%.

[0176] Example 6

[0177] The filling material was prepared according to the method of Example 1, with the only difference being that the mass proportion of water in the epoxy soybean oil-modified silica that adsorbed water was 20%.

[0178] Example 7

[0179] The filling material was prepared according to the method of Example 1, except that the mass ratio of the epoxy soybean oil to the white carbon black in the epoxy soybean oil-modified white carbon black that adsorbed water was 1:2.

[0180] Example 8

[0181] The filling material was prepared according to the method of Example 1, except that the mass ratio of the epoxy soybean oil to the white carbon black in the epoxy soybean oil-modified white carbon black that adsorbed water was 1:7.

[0182] Example 9

[0183] The filling material was prepared according to the method of Example 1, except that the mass fraction of EPDM rubber was 40 parts, that is, the mass ratio of EPDM rubber to water-absorbed epoxidized soybean oil-modified silica was 1.14:1.

[0184] Example 10

[0185] The filling material was prepared according to the method of Example 1, with the only difference being that the mass fraction of EPDM rubber was 14 parts, that is, the mass ratio of EPDM rubber to water-absorbed epoxidized soybean oil-modified silica was 0.4:1.

[0186] Embodiment 11

[0187] The filling material was prepared according to the method of Example 1, with the only difference being that the mass fraction of calcium carbonate was 55 parts and the mass fraction of carbon black was 20 parts, that is, the mass ratio of the water-absorbed epoxy soybean oil-modified white carbon black to the second filler (the second filler was carbon black and calcium carbonate) was 0.46:1.

[0188] Comparative Example 1

[0189] The filling material was prepared according to the method of Example 1, with the only difference being that the silica was not modified with epoxidized soybean oil, and the epoxidized soybean oil-modified silica that absorbed water in the preparation raw materials of the filling material was replaced with 30 parts of silica that absorbed 15% water and 5 parts of epoxidized soybean oil.

[0190] Comparative Example 2

[0191] The filling material was prepared according to the method of Example 1, with the only difference being that the epoxy soybean oil-modified silica does not absorb water, and the epoxy soybean oil-modified silica that absorbs water in the preparation raw material of the filling material was replaced with 35 parts of epoxy soybean oil-modified silica.

[0192] Comparative Example 3

[0193] The filling material was prepared according to the method of Example 1, except that the epoxy soybean oil-modified white carbon black that absorbed water in the preparation raw materials of the filling material was replaced with 30 parts of white carbon black that absorbed 15% of water and 5 parts of dioctyl phthalate DOP.

[0194] Comparative Example 4

[0195] The filling material was prepared according to the method of Example 1, with the only difference being that the epoxy soybean oil-modified silica that absorbs water in the preparation raw material of the filling material was replaced with 29.75 parts of epoxy soybean oil-modified silica and 5.25 parts of water.

[0196] A cable was prepared using the filling materials prepared in the above embodiments and comparative examples. The model of the cable was FDEH-40, 26 / 35kV, 3X150+3X50.

[0197] The performance tests of the filling materials prepared in the above embodiments and comparative examples include:

[0198] Tensile strength and elongation at break of filling materials: tested according to GB / T2951 method, the test results are shown in Table 1.

[0199] Cable torsion resistance test: GB / T33606-2017 Appendix B, the test results are shown in Table 2.

[0200] Table 1

[0201]

[0202] Table 2

[0203]

[0204] Among them, "passed" means that under the corresponding torsion conditions, neither the filling material nor the core of the cable is broken; "filling broken" means that under the corresponding torsion conditions, the filling material in the cable is broken, but the core is not broken; "core broken" means that under the corresponding torsion conditions, both the filling material and the core of the cable are broken.

[0205] From the above table we can see that:

[0206] (1) Compared with Examples 4-6, it can be seen that the present application controls the adsorption amount of the foaming agent in the first filler to ensure a uniform microporous structure and improve the physical and mechanical properties of the filling material.

[0207] (2) Compared with Examples 7-8, it can be seen that the present application controls the mass ratio between epoxidized soybean oil and white carbon black, which not only makes the filling particles well dispersed during the preparation of the filling material, but also ensures that the surface functional groups of the first filler are tightly combined with the rubber matrix.

[0208] (3) Compared with Examples 9-10, it can be seen that the present application controls the mass ratio of the rubber substrate to the first filler, thereby having better mechanical properties, low temperature properties and torsion resistance.

[0209] (4) Compared with Example 1 and Example 11, it can be seen that the present application controls the mass ratio of the first filler to the second filler to ensure rubber cross-linking and improve the mechanical properties, low temperature properties and torsion resistance of the filling material.

[0210] (5) Compared with Comparative Examples 1-3, it can be seen that the present application uses a rubber material as a base material and disperses a filler that can cross-link with the rubber base material to form a filling material with a porous structure. This can not only reduce the overall mass of the filling material, but also improve the torsional fatigue resistance due to the presence of the pore structure during the torsion process, reduce the impact of vibration on the wire core, and increase the service life of the cable.

[0211] (6) Compared with Example 4, it can be seen that in the present application, the foaming agent is adsorbed on the first filler. The foaming agent can be evenly mixed in the raw material as the first filler is dispersed, so that the formed porous structure is more uniform. Moreover, the foaming agent adsorbed in the first filler can be released in stages, so that the pore structure of the porous structure is evenly dispersed and the pore structure size is small, thereby avoiding the accumulation of the foaming agent leading to uneven dispersion of the pore structure or excessive pore structure.

[0212] To sum up, the present application adopts a filling material with a porous structure, which can reduce the overall weight of the cable and reduce the difficulty of cable lifting. The porous structure can play a shock-absorbing and buffering role during the cable torsion process, effectively protect the wire core and increase the service life. Moreover, the filling material of the present application can effectively prevent the cable from brittle fracture in a low temperature environment, and still has good anti-fatigue performance at low temperature (-40°C).

[0213] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0214] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A filling material, characterized in that: The filling material has a porous structure, and includes a rubber base material and a first filler dispersed in the rubber base material, the first filler is cross-linked with the rubber base material, and a mass ratio of the rubber base material to the first filler is (0.45-1):1; The first filler includes filler particles and a modifier grafted on the surface of the filler particles, the modifier is cross-linked with the rubber substrate; the filler particles include at least one of white carbon black, montmorillonite, illite, bentonite, kaolin and clay; the modifier includes at least one of epoxidized soybean oil, epoxidized linseed oil and epoxidized rapeseed oil; the mass ratio of the modifier to the filler particles is 1:(3-8); The filling material further contains a second filler dispersed in the rubber substrate; the second filler includes at least one of calcium carbonate, carbon black, talcum powder and clay; the mass ratio of the first filler to the second filler is (0.5-1.8):1; The preparation method of the filling material comprises the following steps: according to the mass parts, 20 to 30 parts of rubber raw materials, 35 to 50 parts of the first filler for absorbing foaming agent, 15 to 60 parts of the second filler, 2 to 3 parts of vulcanizing agent, 1 to 2 parts of antioxidant, 5 to 11 parts of activator, 1 to 3 parts of plasticizer and 1 to 2 parts of coupling agent are mixed to prepare the filling material; The mass content of the foaming agent in the first filler for absorbing the foaming agent is 10% to 15%, and the foaming agent includes water.

2. The filling material according to claim 1, characterized in that The filling material satisfies at least one of the following conditions: (1) The porosity of the filling material is 10% to 50%; (2) The average diameter of the pore structure in the filler material is 1 mm to 2 mm; (3) The rubber substrate includes at least one of ethylene propylene rubber, natural rubber, styrene butadiene rubber, chlorinated polyethylene rubber, silicone rubber and ethylene-vinyl acetate copolymer.

3. A method for preparing a filling material, characterized in that: The preparation method of the filling material comprises: According to the weight ratio, 20 to 30 parts of rubber raw materials, 35 to 50 parts of the first filler for absorbing foaming agents, 15 to 60 parts of the second filler, 2 to 3 parts of vulcanizing agents, 1 to 2 parts of antioxidants, 5 to 11 parts of activators, 1 to 3 parts of plasticizers and 1 to 2 parts of coupling agents are mixed to prepare the filling material; Wherein, the mass content of the foaming agent in the first filler for absorbing the foaming agent is 10% to 15%, and the foaming agent includes water; The filling material has a porous structure, and includes a rubber substrate and a first filler dispersed in the rubber substrate, the first filler is cross-linked with the rubber substrate, and the mass ratio of the rubber substrate to the first filler is (0.45~1):

1. The first filler includes filling particles and a modifier grafted on the surface of the filling particles, and the modifier is cross-linked with the rubber substrate; the filling particles include at least one of white carbon black, montmorillonite, illite, bentonite, kaolin and clay; the modifier includes at least one of epoxidized soybean oil, epoxidized linseed oil and epoxidized rapeseed oil; the mass ratio of the modifier to the filling particles is 1:(3~8); the filling material also contains a second filler dispersed in the rubber substrate; the second filler includes at least one of calcium carbonate, carbon black, talc and clay; the mass ratio of the first filler to the second filler is (0.5~1.8):

1.

4. Use of the filling material according to claim 1 or 2 in the preparation of power transmission products.

5. A cable, characterized in that: The cable comprises the filling material according to claim 1 or 2.

Citation Information

Patent Citations

  • Rubber composition, preparation method thereof and sealing strip

    CN115785577A